O tempo vertical e a dimensão do poético na obra de Clarice Lispector: uma leitura bachelardiana - Oliveira, Maria Elisa de [UNESP] (Universidade Estadual Paulista (Unesp), Departamento de Filosofia, 1993)
A presença marcante de uma prosa-poética na produção ficcional de Clarice Lispector possibilitou-nos exemplificar algumas noções centrais (tempo vertical e instante poético) na rica e sugestiva reflexão de Gaston Bachelard acerca do universo poético

The remarkable presence of a poetic-prose in Clarice Lispector's fictional artistic creation gave us the possibility of exemplifying some central aspects, as vertical time and poetic instant, in Gaston Bachelard's rich and suggestive reflexion about the poetic universe.
The vertical time and the poetic's dimension in Clarice Lispector's fictional artistic creation: a bachelardian analysis
Keywords: Tempo vertical; tempo presente; instante poético; prosa-poético; literatura; Vertical time; present time; poetic instant; poetic-prose literature